CHARACTERIZATION OF CARBOXYMETHYL CELLULOSE (CMC) FROM PALM MIDRIB - Devi Silsia; Zulman Efendi; Febri Timotius (Jurnal Agroindustri, 2018)
Midrib is one of the palm plantation  waste that has not been utilized optimally. The high cellulose content of palm midrib is potentially converted to carboxymethyl cellulose. This study aims to determine the characteristics of carboxymethyl cellulose that produced from various concentrations of trichloroacetic acid and reaction times. This study used a complete randomized design (RAL) with two factors i.e tricloroacetic acid concentration (10%, 20% and 30%) and reaction time (3 hours and 4 hours). The synthesis of carboxymethyl cellulose in this study consists of three stages i.e alkalization, carboxymethylation and purification. The carboxymethyl cellulose obtained was characterized include degree of subsitution (DS), pH, viscosity, water content, and purity. The results showed that the best carboxymethyl cellulose was obtained from the use of 20% tricloroacetic acid and 3 hours reaction time. The characterrization result include substitution degree value of 0.76, pH of 8.32, water content of 7.1%, with a  viscosity of 7.8 cP,   and purity of 92.62%.